The Relationship Between Excessive Gadget Use and Sleep Patterns Among Students - Putri Sari, Ameza; Oktavia, Santi; Nurwinda, Nova (Java Nursing Journal, 2025)
Background: The increasing accessibility and utility of gadgets among adolescents raise growing concerns about their impact on health, particularly sleep patterns. Excessive gadget use, especially during nighttime, has been linked to various sleep disturbances in school-aged children. Purpose: This study aimed to determine the relationship between excessive gadget use and sleep pattern disturbances among students at SMP Negeri 14 Bandar Lampung in 2024. Methods: A cross-sectional analytical survey was conducted involving 282 students from the 7th and 8th grades. Stratified random sampling was used, and data were collected using a structured questionnaire assessing gadget use and sleep quality. The Chi-square test was employed to evaluate the statistical association between the variables. Results: Among the respondents, 62.1% exhibited moderate gadget use, while 55.7% experienced moderate insomnia. The analysis revealed a statistically significant association between the level of gadget usage and the severity of sleep disturbances (p < 0.001). Notably, students with high gadget use were more likely to report insomnia symptoms. Conclusion: The findings underscore a significant correlation between excessive gadget usage and disrupted sleep patterns among adolescents. Early intervention through parental guidance and institutional policies is essential to mitigate the adverse effects of gadget overuse on student health and academic performance.